CRITICA A LOS PRINCIPIOS FUNDAMENTALES DE LA FISICA: EL PROBLEMA DE LA PARTICULA ELEMENTAL - Monroy Cárdenas, Oscar S. (2006)
When reviewing the concept of indivisible elementary particle, as a basic component of matter, we face contradictions with the principles of the conventional physics theories. The primary concept of elementary particle may be the cause of the confusion and hindering of the fundamental tasks of the physicist on.